New species of Liolaemus (Reptilia, Squamata, Liolaemini) of the Liolaemus donosobarrosi clade from northwestern Patagonia, Neuquén province, Argentina - Avila, Luciano Javier; Perez, Cristian Hernán Fulvio; Minoli, Ignacio; Medina, Cintia Debora; Sites, Jack W. Jr.; Morando, Mariana (Zootaxa, 2017)
Two new species of the Liolaemus donosobarrosi clade are described. Liolaemus tirantii sp. nov. and Liolaemus calliston sp. nov. differ from other members of their clade by a combination of coloration characters, morphometric and molecular traits. Liolaemus tirantii sp. nov. is known from three localities separated only a few kilometers from each other and Liolaemus calliston sp. nov. is known only from the type locality. Both species inhabit a region strongly impacted by oil and gas extraction but their conservation status is unknown.